2020
DOI: 10.1021/jacs.9b12377
|View full text |Cite
|
Sign up to set email alerts
|

High-Entropy Perovskite Fluorides: A New Platform for Oxygen Evolution Catalysis

Abstract: High-entropy perovskite fluorides (HEPFs) have great potential in electrocatalysis that has not been realized because of the limitation of a high-temperature synthetic route and the limited understanding of high-entropy materials. The use of HEPFs in effective oxygen evolution catalysis and a feasible synthesis route for HEPFs in a boiled solution by combining a hydrothermal method with mechanochemistry are first reported here. These HEPFs consisting of cost-effective elements dramatically gave excellent catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
195
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(208 citation statements)
references
References 45 publications
0
195
0
Order By: Relevance
“…Using cheap metal sulfates instead of expensive fluorides, Dai and coworkers manufactured a class of ABF 3 -type potassium-based HEP fluorides (K-HEPFs) with a single perovskite phase. [45] A dual-phase perovskite, TiZrHfNbTaO 11 , including 60 mol% AB 2 O 7 monoclinic perovskite and 40 mol% of A 6 B 2 O 17 orthorhombic perovskite, was synthesized by mechanochemistry followed by high-pressure torsion method and high-temperature oxidation. [46] This two-phase oxide showed an appreciable light absorbance in the visible-light region with an appropriate valence and conduction bands for water splitting.…”
Section: Mechanical Alloying Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using cheap metal sulfates instead of expensive fluorides, Dai and coworkers manufactured a class of ABF 3 -type potassium-based HEP fluorides (K-HEPFs) with a single perovskite phase. [45] A dual-phase perovskite, TiZrHfNbTaO 11 , including 60 mol% AB 2 O 7 monoclinic perovskite and 40 mol% of A 6 B 2 O 17 orthorhombic perovskite, was synthesized by mechanochemistry followed by high-pressure torsion method and high-temperature oxidation. [46] This two-phase oxide showed an appreciable light absorbance in the visible-light region with an appropriate valence and conduction bands for water splitting.…”
Section: Mechanical Alloying Methodsmentioning
confidence: 99%
“…HEAs can be manufactured by physical mixing and mechanical alloying methods through ball milling of the metal powders with the process controlling agents. [ 18,25,43–46 ] A composite of HEA‐NPs and few‐layer graphene was first reported by Rekha et al via ball milling process following the graphene exfoliation. [ 47 ] The as‐synthesized NiCrCoCuFe HEA‐NPs showed a FCC structure and the composite exhibited excellent corrosion resistance.…”
Section: Synthesis Strategies Of Hem‐npsmentioning
confidence: 99%
“…Inorganic metal fluorides find applications in catalysis, as electrode active materials, as superconducting devices, as corrosion protection etc. [18][19][20][21] Non-binary compounds, like Co doped MgF 2 , can show additional properties, like in the mentioned case the modification of surface acidity properties whilst maintaining the rutile phase. 22 Ternary metal fluorides for instance, AgCuF 3 , 23 Cu x Fe 1-x F 2 or Li 3 MF 6 (M=V, Cr, Mn, Co, Fe) demonstrate reversible conversion reactions with Li-ions, [24][25][26] rendering them as potential energy storage materials.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 First reports about rare-earth-based fluorite and perovskite structured high entropy fluorides and rock-salt structured oxyfluorides have shown promising properties for energy storage, optical and catalytic properties. 6,16,18 Wang et al reported that the existence of weak bonds between transition metal (TM)fluoride species, intrinsic structural defects and a distortion of the HEM lattice due to different TM constituents, can provide enhanced oxygen evolution reaction (OER) activity. 18 Due to their special electronic configuration and surface complexity, HEMs are in general expected to provide desirable electrocatalytic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation